Photoreactions of Endohedral Metallofullerene with Siliranes: Electronic Properties of Carbosilylated Lu3N@Ih-C80 - Masahiro Kako; Kazuya Minami; Taiki Kuroiwa; Shinpei Fukazawa; Yuki Arikawa; Michio Yamada; Yutaka Maeda; Qiao-Zhi Li; Shigeru Nagase; Takeshi Akasaka (Molecules, 2017)
Photochemical carbosilylation of Lu3N@Ih-C80 was performed using siliranes (silacyclopropanes) to afford the corresponding [5,6]- and [6,6]-adducts. Electrochemical studies indicated that the redox potentials of the carbosilylated derivatives were shifted cathodically in comparison with those of the [5,6]-pyrrolidino adducts. The electronic effect of the silirane addends on Lu3N@Ih-C80 was verified on the basis of density functional theory calculations.